Sheep know-all - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Sheep By R M Gatenby, The Tropical Agriculturalist, CTA Macmillan, 2002. 184 pp. ISBN 0 333 79881 3 CTA number 304. 10 credit points